Implementasi Model Pembelajaran Kooperatif Tipe Jigsaw dalam Meningkatkan Partisipasi Belajar Siswa Kelas VIII pada Mata Pelajaran PAI di SMP Negeri 1 Rangsang Barat - Irvan Afandi; Risnawati Risnawati; Miftahir Rizqa (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This article is entitled "Implementation of the jigsaw type cooperative learning model in increasing the learning participation of eighth grade students in PAI subjects at SMPN 1 Rangsang Barat". The Jigsaw Type Cooperative learning model is a type of cooperative learning consisting of several members in one group who are responsible for mastery. part of the learning material and being able to teach the material to other people in the group. The aim of this research is to reveal the implementation of the Jigsaw Type Cooperative Learning Model in increasing student learning participation at SMP Negeri 1 Rangsang Barat, therefore the author formulates a problem formulation, namely How to Implement the Learning Model Jigsaw Type Cooperative in increasing student learning participation at SMP Negeri 1 Rangsang Barat. This type of research is library research using descriptive qualitative percentages. From the results of this research is observation data on the implementation of the Jigsaw Type Cooperative Learning Model in increasing student learning participation at SMP Negeri 1 Rangsang Barat based on the results of 6 observation data at a level of 77%. With the percentage of observation data results, it can be concluded that it is in the effective category. And it is necessary to implement the jigsaw cooperative learning model which requires teacher activities in the form of: Providing motivation, dividing into groups, monitoring activities, providing texts and providing assessments.